Latency Strategies of Herpesviruses - Minarovits, Janos.; Minarovits, Janos.; Gonczol, Eva.; Gonczol, Eva.; Valyi-Nagy, Tibor.; Valyi-Nagy, Tibor. (Springer US : Imprint: Springer, 2007)
Latency is a fascinating property of herpesviruses which ensures the maintenance of their genetic information in their hosts for an extended period in the absence of productive virus replication. Focusing on human herpesviruses and animal models of herpesvirus-associated human diseases, this is the first book dealing with the intricate epigenetic mechanisms (DNA methylation, histone modification, alteration of chromatin structure) that regulate latency-associated transcription. Special attention is given to immune evasion "tricks" blocking immune responses to herpesvirus infected cells and viral RNAs and proteins involved in malignant transformation. Latency Strategies of Herpesviruses is an ideal book for researchers, scientists and graduate students in the fields of virology, immunology, microbiology, bacteriology, and veterinary medicine.